Management oral care mengatasi mucositis pada pasien kanker yang menjalani terapi kemo dan radiasi: A systematic review - Siregar, Ngolu; Putri, Yosie Susanti Eka; Nuraini, Tuti (Holistik Jurnal Kesehatan, 2025)
Background: Oral mucositis (OM) is a common and highly symptomatic complication of cancer therapy that affects the quality of life function. Chemotherapy and radiation are the most widely used interventions in cancer treatment. The prevalence of oral mucositis side effects among 294 head and neck cancer patients was 93.9%. Purpose: To analyze oral care management to overcome mucositis in cancer patients undergoing chemotherapy and radiation therapy. Method: Literature review study using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and PICOS approach, P: cancer patients undergoing chemotherapy and radiation, I: oral care management, C: no specific treatment or other standard care, O: reducing severity and accelerating healing, S: randomized controlled trial (RCT). Literature search using keywords “management” AND "oral mucositis" OR “stomatitis” OR “oromucositis” OR “oromucositides” AND "cancer", “management” AND “mucositis” OR “oral mucositis” OR “mucosa inflammation” OR “stomatitis” AND “cancer treatment”. Results: Various methods have been used to treat oral mucositis in cancer patients undergoing chemotherapy and radiation. Although there are differences in the timing, method, and frequency of mouthwash use, most of the literature shows that mouthwash is effective in reducing oral mucositis in patients. Conclusion: Management of oral mucositis can be done to treat and prevent oral mucositis in cancer patients currently receiving chemo and radiation therapy.   Keywords: Cancer; Chemotherapy; Mucositis Oral; Radiotherapy.   Pendahuluan: Oral mucositis (OM) merupakan komplikasi umum dan sangat simtomatik dari terapi kanker yang memengaruhi fungsi kualitas hidup. Kemoterapi dan radiasi adalah intervensi paling banyak digunakan dalam pengobatan kanker. Prevalensi efek samping mukositis oral diantara 294 pasien kanker kepala dan leher adalah 93.9%. Tujuan: Untuk menganalisis management oral care mengatasi mucositis pada pasien kanker yang menjalani terapi kemo dan radiasi. Metode: Penelitian literature review menggunakan panduan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) dan pendekatan PICOS, P: pasien kanker yang menjalani kemoterapi dan radiasi, I: manajemen perawatan oral, C: tidak ada perawatan khusus atau perawatan standar lainnya, O: mengurangi keparahan dan mempercepat penyembuhan, S: randomized control trial (RCT). Pencarian literatur menggunakan kata kunci “management” AND "oral mucositis" OR “stomatitis” OR “oromucositis” OR “oromucositides” AND "cancer", “management” AND “mucositis” OR “oral mucositis” OR “mucosa inflammation” OR “stomatitis” AND “cancer treatment”. Hasil: Berbagai metode telah digunakan untuk mengatasi mukositis oral pada pasien kanker yang menjalani kemoterapi dan radiasi. Meskipun terdapat perbedaan dalam waktu, cara, dan frekuensi penggunaan obat kumur, sebagian besar literatur menunjukkan bahwa obat kumur efektif dalam mengurangi mukositis oral pada pasien. Simpulan: Manajemen penanganan mukositis oral dapat dilakukan untuk mengatasi dan mencegah mukositis oral pada pasien kanker yang menjalani terapi kemo dan radiasi.   Kata Kunci: Kanker; Mukosisitis Oral; Radiasi; Terapi Kemo.